2017
DOI: 10.1093/ejcts/ezx409
|View full text |Cite
|
Sign up to set email alerts
|

Results of repeated video-assisted thoracic surgery for recurrent pneumothorax after primary spontaneous pneumothorax

Abstract: Repeated VATS was a feasible method to treat recurrent PSP after VATS for PSP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…Recently, numerous etiologies of recurrent pneumothorax following VATS have been proposed. While missed bullae have been recognized as the reason for recurrent pneumothorax following VATS, new bullae formation is now being considered an important etiology (4)(5)(6)(7). We have previously reported that higher tension in the staple line which was associated with bulky resection during VATS, increased the risk of recurrence (7).…”
Section: Original Articlementioning
confidence: 99%
“…Recently, numerous etiologies of recurrent pneumothorax following VATS have been proposed. While missed bullae have been recognized as the reason for recurrent pneumothorax following VATS, new bullae formation is now being considered an important etiology (4)(5)(6)(7). We have previously reported that higher tension in the staple line which was associated with bulky resection during VATS, increased the risk of recurrence (7).…”
Section: Original Articlementioning
confidence: 99%
“…Muramatsu et al reported that the new bulla formation was the most common recurrence factor after VATS bullectomy alone for PSP (8). Cho et al observed that the most common reason for recurrent PSP after VATS was the formation of a bulla on the previous staple line, followed by a new bulla formation in a location other than the staple line (9). In our previous study, younger patients aged <25 exhibited a higher tendency for detection of postoperative bulla neogenesis on the staple line using HRCT, significantly (10).…”
Section: Discussionmentioning
confidence: 60%
“…However, it has recently been suggested that younger patients have a higher postoperative recurrence (21.9-27.9%) of pneumothorax than older patients, even if the same procedures for prevention of the postoperative Original Article Contralateral bulla neogenesis associated with postoperative recurrences of primary spontaneous pneumothorax in young patients recurrence are performed (4-7). Bulla neogenesis is thought to be the main reason for postoperative recurrence (8)(9)(10). In addition, it was reported that young patients aged <20 years frequently developed bulla neogenesis regardless of surgical treatment (11).…”
Section: Introductionmentioning
confidence: 99%
“…However, based on a study on chest computed tomography images acquired 1 year after surgery, Onuki et al reported that although the PGA covering reduced the SP recurrence rate, it did not prevent neogenetic bullae occurrence 31 . In a study comparing absorbable mesh covering with mechanical pleurodesis, Cho et al reported no difference in the frequency of new bullae; however, the PGA covering group exhibited a slightly reduced frequency of bullae occurrence at the staple line compared with mechanical pleurodesis 34 . Ten studies included in the present meta-analysis discussed the cause of recurrence 12,13,15,17,18,23,24,30,31 ; of these, seven concluded that the area along the staple line was not a cause of postoperative recurrence 12,13,15,18,24,30,31 .…”
Section: Discussionmentioning
confidence: 99%